Effect of conservation agriculture on soil hydro-physical properties, total and particulate organic carbon and root morphology in wheat (Triticum aestivum) under rice (Oryza sativa)-wheat system - MONDAL, SURAJIT; DAS, T K; THOMAS, PAULSON; MISHRA, A K; BANDYOPADHYAY, K K; AGGARWAL, PRAMILA; CHAKRABORTY, DEBASHIS (The Indian Journal of Agricultural Sciences, 2019)
Short-term (5 years) effect of conservation agriculture (CA) practice on soil hydro-physical characteristics, soil organic carbon status and root morphology in wheat (triticum aestivum L.) was monitored under rice (Orgza sativa L.)-wheat rotation in a clay loam soil at the Indian Agricultural Research Institute, New Delhi. A small improvement in soil water content and a marginal decrease in bulk density by CA contributed in significant reduction (30-37%) in sub-surface compaction. The CA improved soil structure in the plough layer (0-15 cm) with significant increase in soil organic carbon status (27-38%). A marginal change in pore size distribution was recorded in favour of larger volume of retention pores (11-12%), in expense of macro- or drainable pore space. Steady-state infiltration, which was essentially profile-controlled, was therefore lower in the CA plots. Decrease in sub-surface soil strength and better soil water retention facilitated root growth in wheat in the sub-surface layer under CA. Results implied that the CA practice in rice-wheat system, although with a shorter period, led to an overall physical improvement of the most active root zone. This had positive impact on root morphology, which contributed to increase in the crop yield.